Editorial - González-Campo, Carlos Hernán (Cuadernos de Administración, 2019)
For the publication of volume 35, issue 64, of Cuadernos de Administración by Universidad del Valle, we have taken several steps in strengthening the dissemination of the knowledge that is brought forward with each new issue, all to continue consolidating ourselves as one of the most relevant publications in the area in Colombia. As a result of the call for this issue, and after a rigorous process of blind evaluation based on the judgment of the selected peers, we have decided to publish 7 papers on this occasion, which we hope will contribute to the expansion of knowledge and serve as drivers for reflection by our readers and reference for authors who are delving into these topics. We extend our gratitude to the members of the Editorial Committee, to the authors and to each of the peer evaluators because, through their work, they contribute to the improvement of our publication and to the dissemination of knowledge above all. The first paper is entitled “Individual unlearning from the point of view of managers in mergers and acquisitions situations in Brazil”, is the result of a research process based on the Brazilian companies managers study method, with mergers and acquisitions; among the results is that many of them have experienced some unlearning. This paper seeks to understand this phenomenon and to make possible its analysis in each context. “Sustainability index, evaluated by University Sustainable Development Units: Colombian University case study”, is the title of the second paper published in this issue. It corresponds to an index proposal constructed with a seven-step methodology. The index serves enterprise-wide decisions, where comparisons and best practices can be achieved. The third paper, “Perceptions of the Colombian business sector in relation to its role in post-conflict scenarios”, is where its authors present a very relevant topic from the perception of entrepreneurs about the “role of the Colombian business sector in the post-conflict and peace-building scenario”. Using quantitative methods, a survey was conducted on 200 companies located in the main cities of Colombia throughout different economic sectors. The results show that there is a willingness to participate in the post-conflict period, but there is a lack of awareness and some concerns about the extent of the participation. “Platforms for SMEs as business models: a user-centric activity system approach” is the fourth paper in this issue, where the authors reflect on the use of web 2.0 tools in SMEs and present their results on the acquisition and retention of users as a business strategy and their relationship with the value proposition and business model. In the fifth paper, “Limited financial rationality by owners or managers of Mexican micro-companies”, the authors propose a hierarchical categorization of the behaviors of the people who make financial decisions, from the analysis of limited rationality and within learning processes within the companies. “Simulation model for the management of internal container transport in a seaport” is the title of the sixth paper of this issue. The proposal seeks to make the containers internal transport process more efficient, incorporating other variables previously not considered directly. Applying the model can achieve increased operator productivity. Finally, the title of the last paper “MBAs and career development: a literature review from the perspective of human capital”, the authors systematize the results of their research on the subject in relevant journals on the effect of pursuing an MBA on management. They analyze three dimensions of human capital and present as a discussion, some implications and the possibility of new research. The content of each of these seven papers is the sole responsibility of their authors. This issue becomes a new opportunity for the national and international scientific community to judge the outcome of each of these proposals.